Trends in multiplicity of Plasmodium falciparum infections among asymptomatic residents in the middle belt of Ghana - Agyeman-Budu Akua (Malaria Journal, 2013)
Abstract Background Malaria is the most important cause of mortality and morbidity in children living in the Kintampo districts in the middle part of Ghana. This study has investigated the multiplicity of infection (MOI) within asymptomatic residents of the Kintampo districts, and the influence of age and seasonality on MOI, by studying the distribution of the polymorphic Plasmodium falciparum antigen merozoite surface protein 2 (MSP2). Methods DNA was extracted from an asymptomatic cohort of children and adults infected with P. falciparum during the period November 2003 to October 2004. Polymerase chain reaction was carried out and multiplicity of infection (MOI) was determined. Results Children under 10 years of age had an average MOI of 2.3 while adults 18 years and above had an average MOI of 1.4. Children below five years had high and low average MOIs of 2.8 in the March/April survey and 0.9 in the May/June survey respectively. A similar trend in the monthly distribution of MOI was observed for the entire cohort. IC/3D7 strains outnumbered the FC27 strains throughout the year by a ratio of about 4:1 with the difference between the prevalence of the two strains being least marked in the March/April survey, at the beginning of the rainy season. MOI was not linked to the level of malaria transmission as measured by the entomological inoculation rate. Discussion/conclusion The impact of interventions, introduced since this baseline study was carried out on the parasite diversity of asymptomatic residents will be the subject of further investigations.